Tackling noncommunicable diseases in Bangladesh : now is the time - El-Saharty, Sameh (Directions in development (Washington, D.C.). Human development., 2013)
Bangladesh is undergoing a double transition-demographic and epidemiological. Increasing life expectancy and declining fertility entail a demographic transition fueling a shift in the disease burden toward noncommunicable diseases (NCDs). Yet due to absence of a robust routine health information system in the country, it is hard to accurately assess the disease burden and corresponding risk factors. So, using a wide range of sources, this book looks at the status of major NCDs in Bangladesh (and briefly in South Asia), touches on their economic impact, analyzes their common risk factors, and a.